A coordinated progression of progenitor cell states initiates urinary tract development - Sanchez-Ferras, Oraly; Pacis, Alain; Sotiropoulou, Maria; Zhang, Yuhong; Wang, Yu Chang; Bourgey, Mathieu; Bourque, Guillaume; Ragoussis, Jiannis; Bouchard, Maxime (Nature communications, 2021)
The kidney and upper urinary tract develop through reciprocal interactions between the ureteric bud and the surrounding mesenchyme. Ureteric bud branching forms the arborized collecting duct system of the kidney, while ureteric tips promote nephron formation from dedicated progenitor cells. While nephron progenitor cells are relatively well characterized, the origin of ureteric bud progenitors has received little attention so far. It is well established that the ureteric bud is induced from the nephric duct, an epithelial duct derived from the intermediate mesoderm of the embryo. However, the cell state transitions underlying the progression from intermediate mesoderm to nephric duct and ureteric bud remain unknown. Here we show that nephric duct morphogenesis results from the coordinated organization of four major progenitor cell populations. Using single cell RNA-seq and Cluster RNA-seq, we show that these progenitors emerge in time and space according to a stereotypical pattern. We identify the transcription factors Tfap2a/b and Gata3 as critical coordinators of this progenitor cell progression. This study provides a better understanding of the cellular origin of the renal collecting duct system and associated urinary tract developmental diseases, which may inform guided differentiation of functional kidney tissue. Nephric duct (ND)-derived ureteric buds (UB) form the kidney collecting duct system, while ureteric tips promote nephron formation. Here the authors use single-cell RNA-seq and introduce Cluster RNA-seq to identify four progenitor populations in developing ND/UB regulated by the transcription factors Tfap2a/b and Gata3.